2017
DOI: 10.1111/1462-2920.13893
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of subzero growth in the cryophile Planococcus halocryophilus determined through proteomic analysis

Abstract: The eurypsychrophilic bacterium Planococcus halocryophilus is capable of growth down to -15°C, making it ideal for studying adaptations to subzero growth. To increase our understanding of the mechanisms and pathways important for subzero growth, we performed proteomics on P. halocryophilus grown at 23°C, 23°C with 12% w/v NaCl and -10°C with 12% w/v NaCl. Many proteins with increased abundances at -10°C versus 23°C also increased at 23C-salt versus 23°C, indicating a closely tied relationship between salt and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 94 publications
2
10
0
Order By: Relevance
“…Interestingly, some bacteria were only able to replicate at temperatures lower than − 6 °C (Tuorto et al 2014 ) and 16S rRNA sequencing demonstrated a greater diversity of active OTUs at subzero temperatures than at 0 °C (Tuorto et al 2014 ). According to a proteomic study, subzero growth (− 10 °C) of Planococcus halocyrophilus from permafrost resulted in a series of complex responses and significant changes in the abundance of proteins involved in various cellular processes, such as synthesis of cell wall, fatty acids, carotenoids, amino acids, energy metabolism, nucleotide turnover, transcription, translation, and DNA replication and repair (Raymond-Bouchard et al 2017 ). This bacterium is able to grow over an exceptionally wide temperature range, from − 15 to 37 °C, and modifies peptidoglycan metabolism (by reducing active peptidoglycan synthesis) and the iron acquisition strategy (by omitting siderophore-mediated iron and preferring ABC-type iron acquisition) after transition from optimal (24 °C) to subzero temperatures (Ronholm et al 2015 ).…”
Section: Microbial Diversity and Activitymentioning
confidence: 99%
“…Interestingly, some bacteria were only able to replicate at temperatures lower than − 6 °C (Tuorto et al 2014 ) and 16S rRNA sequencing demonstrated a greater diversity of active OTUs at subzero temperatures than at 0 °C (Tuorto et al 2014 ). According to a proteomic study, subzero growth (− 10 °C) of Planococcus halocyrophilus from permafrost resulted in a series of complex responses and significant changes in the abundance of proteins involved in various cellular processes, such as synthesis of cell wall, fatty acids, carotenoids, amino acids, energy metabolism, nucleotide turnover, transcription, translation, and DNA replication and repair (Raymond-Bouchard et al 2017 ). This bacterium is able to grow over an exceptionally wide temperature range, from − 15 to 37 °C, and modifies peptidoglycan metabolism (by reducing active peptidoglycan synthesis) and the iron acquisition strategy (by omitting siderophore-mediated iron and preferring ABC-type iron acquisition) after transition from optimal (24 °C) to subzero temperatures (Ronholm et al 2015 ).…”
Section: Microbial Diversity and Activitymentioning
confidence: 99%
“…In another bacterium isolated from permafrost— Exiguobacterium sibiricum —the presence of methylglyoxal synthase was proposed by Rodriguez et al [ 10 ] as an important feature for bypassing the lower part of glycolysis, since it is an alternative catabolic pathway for triose phosphates. Glyoxalase family proteins have also been recognized as key components in Planococcus halocryophilus Or1, a non-spore forming Firmicutes isolated from subzero temperatures from high Arctic permafrost [ 12 ]. The breakdown of glyoxal and methylglyoxal, formed as by-products of several metabolic pathways under subzero conditions, allows the removal of reactive electrophilic species through the recycling of reactive carbonyls to lactate, which is further used for cellular metabolism [ 12 ].…”
Section: Metabolic Features Related To Energy Generation In Cold Ementioning
confidence: 99%
“…Glyoxalase family proteins have also been recognized as key components in Planococcus halocryophilus Or1, a non-spore forming Firmicutes isolated from subzero temperatures from high Arctic permafrost [ 12 ]. The breakdown of glyoxal and methylglyoxal, formed as by-products of several metabolic pathways under subzero conditions, allows the removal of reactive electrophilic species through the recycling of reactive carbonyls to lactate, which is further used for cellular metabolism [ 12 ]. These results were in line with previous work, showing that, in this bacterium, energy metabolism was repressed at −15 °C.…”
Section: Metabolic Features Related To Energy Generation In Cold Ementioning
confidence: 99%
“…This bacterial strain shows many cold and osmotic stress responses such as the expression of cold-adapted proteins, the expression of various osmolyte transporters, a high lipid turnover rate, a high resource efficiency at cold temperatures with an accumulation of carbohydrates as a energy resource (Mykytczuk et al , 2013 ), and complex changes in protein abundances (Raymond-Bouchard et al , 2017 ). Furthermore, under cold growth conditions, P. halocryophilus develops a nodular sheet-like crust around the cells (Ronholm et al , 2015 ; Mykytczuk et al , 2016 ).…”
Section: Introductionmentioning
confidence: 99%